Randomized clinical trial comparing different methods of bowel preparation using oral sodium phosphate for day -care colonoscopy - Wei, Teoh boon (2007)
Objectives: To compare two different timings for a similar bowel preparation agent (oral sodium phosphate, NaP) and determine the quality of bowel cleansing plus patient tolerance, compliance and acceptability. Methodology: This is a prospective randomized clinical trial involving 97 out-patients attending the surgical clinic of Penang Hospital who were planned for elective colonoscopy. All eligible patients who agreed to participate were randomized into two groups (one group was required to take NaP at a 4-hour interval ( 1500h and 1900h on the day before the colonoscopy) and another group at a 12-hour interval (1800h on the day before the colonoscopy and 0600h on the day of the colonoscopy). Instructions for bowel preparation were given accordingly. The subjects were given a questionnaire to complete prior to their procedure. After the procedure, the colonoscopists (who were blinded to the patients' assigned group) were in turn given a questionnaire to fill. Data were then collected and compiled for analysis. Results: There was equal distribution of male and female patients for both groups with an average age of 52.5 years. The commonest indication for elective colonoscopy was for altered bowel habits, followed by bleeding, abdominal pain or discomfort, screening and finally anaemia. Of the side-effects questioned, none differed significantly from each other. Most patients tolerated both bowel preparations well with a median total patient score of 6 out of a possible maximum score of 24. However, patients who took NaP over two days (Group 2) had significantly more incidence of postural hypotension than the other group which took NaP over one day (Group 1 ). Group 2 patients also had more number of bowel movements (10.46 ± 5.32 versus 7.96 ± 3.24 in Group 1) and found it harder to complete their bowel preparation. Even then, Group 2 patients were just as willing as Group 1 patients to take the same bowel preparation again if colonoscopic examination was required in the future. Total score for quality of bowel preparation was 3.17 ± 2.97 in Group 2 as opposed to 4.90 ± 2.98 in Group 1. That means overall, Group 2 patients had better bowel cleansing than Group 1 patients. Conclusion: With other factors such as gender, age and indication for colonoscopy neutralized by randomization, it was found that the incidence of side-effects following either bowel preparation regimen is the same except for postural hypotension which is more common in Group 2 patients. Group 2 patients also had more bowel movements and that is why they found it harder to complete their bowel preparation. Since Group 2 patients had more bowel movements, they also had the better prepared bowel. If the effects of posturalhypotension caused by hypovolemia can be negated by increased fluid consumption, we would find that taking NaP over the course of two days would definitely be superior. However, it is recommended that this method be prescribed selectively for fit patients with no major medical illness and ultimately, clinical discretion need to be employed to decide on the appropriate bowel preparation method for a particular patient.